(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Insecure and undocumented movement both within and across countries has been linked to arise in trafficking. Many individuals in rural India are leaving their homes and moving to the cities in questof better economic prospects or to escape poverty. Forced bonded labour, child labor, forced marriages,sexual commercial exploitation, bonded labor, etc. all play a role in this pattern, which involves massivemigration of children and women. The number of missing children and women who are later shown tohave been trafficked is a topic that is in the news almost daily. Hundreds of unlicensed placement firmsthrive in the nation’s capital, Delhi, to meet the high need for domestic workers willing to put in extrahours if needed. Younger children are preferred by employers despite their illegal age since they are lessexpensive, make fewer complaints, and may be exploited in any way the employer sees fit. The dark lifeof big cities forces these women and children, especially the girl child, to a fate not unlike hell. This isespecially true for those whose home countries are hit hard by poverty, natural disasters like flood ordrought, a lack of employment opportunity, or a lack of education. In their 2013 study Current Situationof Victim Support Providers and Criminal Justice Players in India, the United Nations Office on Drugsand Crime (UNODC) noted that Delhi was becoming a major hub or transit point for sex trafficking. Inaddition to red light districts, sex trafficking occurs at hotels, guesthouses, and massage parlorswhere clients feel most comfortable and where they may spend the least amount of money. People fromthe Bedia, Nat, and Kanjar tribes, among others, are shown in the study to keep females in secludedregions on the outskirts of the city along the NCR and then sell them for profit once they reach puberty.Garstin Bastion Road, often known as G.B. Road or The land of Pink Nipples, is the largest red-lightdistrict in Delhi.